Synthesis, characterization, and hyperpolarizability measurements of main-chain azobenzene molecules - Smitha, P.; Asha, S. K.; Pillai, C. K. S. (Journal of Polymer Science Part A: Polymer Chemistry, 2005)
A series of new AB type azobenzene monomers based on various substituted phenols and higher order fused/extended aromatic rings were synthesized and their hyperpolarizability tensor β determined by hyper-Rayleigh scattering (HRS) measurement in methanol. The electron donor ([BOND]OH) and acceptor units ([BOND]COOH) were kept constant in the series, but the effective conjugation length was varied by varying the number and position of substituents as well as the number of aromatic rings. The effect of substitution of the phenolic ring on the β value was investigated and it was found to range from 15 × 10−30 to 42 × 10−30 esu. The effect of intramolecular hydrogen bonding on the nonlinear optical (NLO) property was also examined. The nonlinearity was in the following order of phenol derivative: α-naphthol > phenyl phenol > 2,6-dimethyl phenol > o-cresol > cardanol > phenol > β-naphthol. The unusually low values for the β-naphthol-based chromophore compared with its isomer (α-naphthol) could be rationalized based on hydrogen bonding of the o-hydroxyl group with the β nitrogen of the azo bridge. These azobenzene NLO chromophoric monomers were polymerized to form main-chain polymers with a head to tail structure. The polymers had high thermal stability and rather low solubility in common organic solvents. © 2005 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 43: 4455–4468, 2005

Structure control for fine tuning fluorescence emission from side-chain azobenzene polymers - Smitha, P.; Asha, S. K. (Journal of Physical Chemistry B, 2007)
New fluorescent azobenzene dyes and side-chain polymers have been synthesized and characterized and their photophysical properties studied. A series of azobenzene dyes having different fluorophores such as phenol (S1), phenylphenol (S2) and naphthol (S3) incorporated in them were synthesized. S2 had unusually high fluorescence with a quantum yield of φf = 0.2 recorded in dichloromethane (DCM), whereas S1 and S3 were found to be weakly fluorescent. The azobenzene dyes were converted into methacrylate monomers having short ethyleneoxy spacers and then free radically polymerized. Phenylphenol-based azobenzene polymer (P2) continued to show fluorescence, whereas fluorescence was completely quenched in the case of phenol (P1)- and naphthol (P3)-based polymers. Phenylphenol, though twisted in the ground state is known to have a more planar geometry in the excited statea factor that enables it to retain its fluorescence behavior even when it is incorporated as part of an azobenzene unit. In contrast, naphthol, which is a better fluorophore compared to phenylphenol, loses much of its emissive behavior upon coupling to the azobenzene unit. The extent of trans to cis photoisomerization in solution was very low (∼17%) for P2 after 30 min of continuous irradiation using 365 nm light, in contrast to ∼ 40% for P1 under identical conditions. This is attributed to the steric repulsion brought about by the bulky phenylphenol units that restrict rotation. A 2-fold enhancement in fluorescence emission was observed for P2 upon irradiation by UV light at 360 nm, which relaxed to the original intensity in about 7 day's time. The higher emission of the cis azobenzenes is generally attributed to an inhibition of photoinduced electron transfer (PET) mechanism. The emission of P2 showed a concentration dependence which increased initially and then decreased in intensity with the formation of a new red-shifted peak at higher concentration due to aggregation. Irradiation of the fluorescence quenched highly concentrated (1 × 10-3 M) sample of P2 showed an enhancement in emission from aggregates at 532 nm.